THE ANALYSIS OF DEVELOPMENT OF BOIM CHICKEN BUSINESS IN MANNA BENGKULU SOUTH - Surya Nengsi; Ahmad Soleh; Novman Ahmad Ali (Penerbit Jurnal Indonesia, 2020)
Marketing strategy is a organized plan in marketing field to obtain maximal result, the strategy in marketing has wide scope in marketing such as strategy in facing competition, pricing strategy, product strategy, service strategy etc. Boim Broiler business at Manna South of Bengkulu support aggressive strategy. The result shows that total power is 19,00 while the weakness is 9,24 so quadrant of internal factors are 19,00-9,24=9,76. It means that Boim broiler business maximize power and minimize weakness in internal. The chance from the strategy is 17,52 and threat is 10,41. So the quadrant of external factor is 17,52 – 10,41 = 7,11 means high ability from Boim broiler business in taking chance and solve the threat in broiling market.